2014
DOI: 10.4236/wjnse.2014.42006
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effect of Silica Nano-Particles with Different Size on Thermotropic Liquid Crystalline Polyester Composites

Abstract: Interface properties of nano-silica/thermotropic liquid crystalline polyesters (TLCP) composites were investigated by X-ray diffraction analysis and differential scanning calorimetory. The crystallinity of TLCP in the composites drastically decreased with an increase of nano-silica content, depending on the surface area of the silica particles. Little size effects (40-400 nm) in the particles and strong interaction between silica surface and the C=O moieties of TLCP were observed by IR analysis. The glass tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…We previously investigated the interfacial regions between PnBA and alumina nanoparticles, 26 and we found that they were enriched with PnBA in a trans ‐ trans conformation. The XRD patterns of PnBA mixed with silica nanoparticles differed from that of neat PnBA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously investigated the interfacial regions between PnBA and alumina nanoparticles, 26 and we found that they were enriched with PnBA in a trans ‐ trans conformation. The XRD patterns of PnBA mixed with silica nanoparticles differed from that of neat PnBA.…”
Section: Resultsmentioning
confidence: 99%
“…The weight percentages of silica nanoparticles in the samples are shown in parentheses. The DSC curve of each sample was normalized based on the weight of the polymer in the sample 25,26 . The DSC curves of neat PnBA and the PnBA/silica composites showed that a glass transition occurred near −54°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curves in the figures were normalized by the polymer weight. [ 24,25 ] The DSC curves of the neat PMMAs in Figures 1‐3 were obtained from the samples prepared by casting PMMA/toluene solutions. The T g values of the neat st ‐, at ‐, and it ‐PMMAs were indicated at 104.0°C, 98.5°C, and 50.8°C on the DSC curve, respectively, and the values were approximately the same as those of the as received samples.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers in parentheses indicate the weight percentages of the nanoparticles in the samples. The curves in the figure were calculated by subtracting the pattern of the nanoparticles from those of the mixed samples [14]. Two main peaks that are characteristic of the XRD pattern of polyacrylates were observed.…”
Section: Introductionmentioning
confidence: 99%